2020
DOI: 10.1111/jan.14318
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mindfulness training on burnout syndrome in nursing: A systematic review and meta‐analysis

Abstract: Aim To analyse the effect of mindfulness training on levels of burnout among nurses. Background Burnout syndrome is a common occupational hazard for nursing staff. Mindfulness training has been proposed as a valid intervention for burnout. Design Systematic review and meta‐analysis. Data sources The CINAHL, LILACS, Medline, ProQuest, PsycINFO, Scielo and Scopus databases were consulted, using the search equation ‘Nurs * AND burnout AND mindfulness’. There was no restriction on the year of publication. Review m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
114
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 97 publications
(210 reference statements)
7
114
1
14
Order By: Relevance
“…Regarding the clinical application of the results, it should be noticed that, for those nurses that have burnout, it is important to implement some intervention that have proven benefit for burnout like mindfulness [ 55 ]. Furthermore, for preventing burnout nursing managers from palliative care units should try to offer social support because it reduce stress and give emotional assistance [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the clinical application of the results, it should be noticed that, for those nurses that have burnout, it is important to implement some intervention that have proven benefit for burnout like mindfulness [ 55 ]. Furthermore, for preventing burnout nursing managers from palliative care units should try to offer social support because it reduce stress and give emotional assistance [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection of a group of midwives exposed to occupational burnout with standardized psychological questionnaires may facilitate the implementation of suitable protective management including: meditation, progressive relaxation, breathing exercises, mindfulness training. A systematic review analysis demonstrated that mindfulness training reduced the levels of burnout [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a recent meta‐analysis by Suleiman‐Martos et al. (2020) found that mindfulness training reduces levels of emotional exhaustion in nurses. Therefore, we hypothesize the following:…”
Section: Introductionmentioning
confidence: 97%
“…A personal resource specifically of interest for nurses dealing with high stress levels and work pressure is mindfulness (White, 2014), a state of self‐regulated attention to the here and now (Brown & Ryan, 2003; Dane, 2011). A growing body of research shows that mindfulness has the potential to reduce perceived stress (Keng et al., 2011) and burnout (Suleiman‐Martos et al., 2020), thereby potentially playing a role in the stress‐related outcomes of work pressure. However, the role of mindfulness as personal resource in the JD‐R model has remained relatively unexplored (Grover et al., 2017; Taylor & Millear, 2016).…”
Section: Introductionmentioning
confidence: 99%